Nephrotic Syndrome: Oedema Formation and Its Treatment With Diuretics - Gupta, Sanjana; Pepper, Ruth J.; Ashman, Neil; Walsh, Stephen B. (Frontiers in Physiology, 2019)
Oedema is a defining element of the nephrotic syndrome. Its’ management varies considerably between clinicians, with no national or international clinical guidelines and subsequent variable outcomes. Oedema may have serious sequelae such as immobility, skin breakdown and local or systemic infection. Treatment of nephrotic oedema is often of limited efficacy, with frequent side-effects and interactions with other pharmacotherapy. Here, we describe the current paradigms of oedema in nephrosis, including insights into emerging mechanisms including the role of the abnormal activation of the epithelial sodium channel in the collecting duct. We then discuss the physiological basis for traditional and novel therapies for the treatment of nephrotic oedema. Despite being the cardinal symptom of nephrosis, few clinical studies guide clinicians to the rational use of therapy. This is reflected in the scarcity of publications in this field; it is time to undertake new clinical trials to direct clinical practice.